Estimativa populacional de muriquis-do-sul (Brachyteles arachnoides, primates, É. Geoffroy 1806) e avaliação da caça no Parque Estadual Carlos Botelho, Continuum Ecológico de Paranapiacaba, São Paulo - Landis, Mariana Bueno [UNIFESP] (2014)
Muriqui is a Atlantic Forest endemic primate and is endangered. Actually, at São Paulo State, the main threat for his survival is the hunting pressure. Probably exist 1300 southern muriquis in nature, but, little is known about your conservation status, especially in continuous forest. This work was delineate to assist actions from Goals 1 and 2 of the National Action Plan for the Muriqui Conservation. For this, was estimated southern muriqui population from the north of Carlos Botelho State Park and was evaluated different areas in function of the occurrence of the hunting pressure and possible variations of habitat conditions. Were also obtained information about hunting occurrence over muriquis. Line transect census was used to estimate population density. Vegetation structural heterogeneity data were used to evaluate if possible differences between three areas could influence in the B arachnoides abundance. Census resulted in 56 muriquis subgroups registrations, in this way was obtained an estimates of 0,16 individuals/ha, estimated for the north of PECB. The southern muriqui density estimated is relatively high if compared with most of the studies done for the genus Brachyteles. Hunting doesn?t seem to influence in the different abundances found, this difference can be explained by habitat differences. Through informers selection method, eight people was interviewed with base in an semi structured script. Were also analyzed reports of the fiscalization operations accomplished by the park keepers and environmental police, from January 2008 to September 2012. The obtained data suggest the presence of two hunters profile: those interested only in the hunting, more frequent in the north of the park, and those that associate the extraction of palm with hunting activity, found in the south. This work brings the first analyses about one of the priority areas for the muriquis conservation, allowing a evaluation of southern muriqui populational status in the north of PECB. It?s observed the need of priority actions for the species conservation. As the hunting is the mean threat for the southern muriqui population, all of the actions elaborated by PAN Muriquis for the enlargement of the fiscalization measures with the purpose of reducing the pressure of the hunt in UCs are indispensable to guarantee the muriquis conservation in PECB.